What matters in practice? Understanding 'quality' in the routine supervision of offenders in Scotland - Grant, Scott (2015)
Little is known about the nature, character and construction of quality in the routine supervision of offenders in Scotland. Quality is an important yet contested concept with multiple facets and features, but its meanings for practitioners are under-researched. This article will present findings from a study using Appreciative Inquiry to reveal how Scottish criminal justice social workers attempt to conceptualise and construct meanings of quality in their daily practice with people who have offended. Our findings conclude that, despite significant fluctuation in criminal justice policy and practice, practitioners' ideas of quality seem to suggest resilience to both managerialism and punitiveness. Practitioners ultimately located quality within relational processes underpinned by social work values, but also saw it as being underscored by (or undermined by the lack of) adequate resourcing, professional supervision, flexibility and training